Factors that influence albuminuria among type 2 diabetes mellitus at primary healthcare clinics in Negeri Sembilan 2007. - S Norma; MT Azmi; AB Rotina (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Introduction: Diabetes Mellitus is a chronic disease and major cause of chronic renal disease. Chronic renal disease can be prevented if known risk factors were been early detected. Albuminuria is the earliest clinical evidence of chronic renal disease. Objectives of this study is to identify the incidence of albuminuria and relationship between albuminuria with socio demographic and clinical factors such as blood sugar control, blood pressure control, excessive body mass index and hypercholesterolemia. Methodology: Data been collected from patient’s record that been regularly follow up at Primary Healthcare Clinics in Negeri Sembilan. Duration of study follow up was from the date of they been diagnosed of Diabetes Mellitus Type 2 until detection of albuminuria or 1st July 2007,end date of data collection then survival analysis been done. Result: Majority of study population was female 60.9% and Malay 69.7%. Mean age was 59.9 ± 10.7 and duration having Diabetes Mellitus was 7.0 ± 6.3 years. Only 22% achieved optimum glucose (HbA1c < 6.5%), controlled blood preassure 130/80 mmHg 42.3%, level of cholesterol <4.5 mmol/L only 22.7 %, 11.4% of patients having ideal body weight < 23 kg/m2. The incidence of Diabetes Mellitus Type 2 was 24.4 cases per 1000 population. The median of follow up duration was 22 years; with minimum follow up was 7 months and maximum 42 years. Survival analysis showed that the median of free albuminuria among cases was 22 years (CI 95%:16.5 – 27.4). The log rank test showed no significant relationship between high blood pressure, excessive body mass index and hypercholesterolemia with albuminuria. This study noted that the occurrence of albuminuria seems to be higher among those were hypertensive (26.6%), and excessive body mass index (24.7%). Conclusion: Percentage of Diabetes Mellitus Type 2 patient that achieved optimum clinical target still very low. Early detection of albuminuria is very important as preventive measure of diabetes nephropathy. Good blood pressure control and ideal bodyweight also prevent of occurring diabetes nephropathy complication.